2012
DOI: 10.1103/physrevstper.8.020105
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis of a Force Concept Inventory data set

Abstract: We perform a factor analysis on a ''Force Concept Inventory'' (FCI) data set collected from 2109 respondents. We address two questions: the appearance of conceptual coherence in student responses to the FCI and some consequences of this factor analysis on the teaching of Newtonian mechanics. We will highlight the apparent conflation of Newton's third law with Newton's first law in one of the FCI questions and suggest an approach to teaching that may avoid this issue. We also note the absence of a distinct fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 32 publications
12
116
1
Order By: Relevance
“…However, we expect that our results can be extrapolated because they are consistent with the results of the interviews with students at Tokyo Gakugei University, Nagoya University, and Meijo University. Further, Thornton et al and Scott et al found similar results for Q.16 [13,14].…”
Section: Range Of Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…However, we expect that our results can be extrapolated because they are consistent with the results of the interviews with students at Tokyo Gakugei University, Nagoya University, and Meijo University. Further, Thornton et al and Scott et al found similar results for Q.16 [13,14].…”
Section: Range Of Resultssupporting
confidence: 66%
“…However, this finding was not considered statistically significant because the number of respondents was insufficient. Scott and colleagues also stated that their hypothesis requires further investigation [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FCI authors proposed a division of the instrument into subcategories [1], but exploratory factor analysis failed to reproduce this division [2,52,53]. More recent analyses have resolved an alternate factor structure [3,48]; however, replication studies are needed to determine if these structures are robust. Because there is not yet a consensus on the FCI factor structure, we did not perform a confirmatory factor analysis.…”
Section: Reliabilitymentioning
confidence: 99%
“…The Force Concept Inventory (FCI) [1] has been studied using tools such as factor analysis [2,3], item response theory [4,5], and network analysis [6]. Though these investigations have probed the structure and validity of the test, they have primarily treated student data as a single undifferentiated sample and have not studied gender effects.…”
Section: Introductionmentioning
confidence: 99%